The Ability of Fluorescent Pseudomonad to Produce Indole Acetic Acid (IAA) - Maysyarah Ardiana; Linda Advinda (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Fluorescent pseudomonads are a group of bacteria derived from the rhizosphere of plants. Fluorescent pseudomonads have potential as plant growth promoters capable of producing Indole Acetic Acid (IAA). This study aims to obtain fluorescent pseudomonad isolates that can produce IAA. The fluorescent pseudomonad isolates used were isolate Pf31 (derived from the rhizosphere of the longan plant), Pf32 (derived from the rhizosphere of the cassava plant), Pf33 (derived from the rhizosphere of the guava plant), Pf35 (derived from the rhizosphere of the galangal plant), Pf36 (derived from the rhizosphere of the guava plant). red ginger), Pf37 (derived from the rhizosphere of the Alocasia plant), Pf38 (derived from the rhizosphere of the celery plant), Pf39 (derived from the rhizosphere of the turmeric plant), and Pf40 (derived from the rhizosphere of the Oxalis plant). namely the detection of the ability of fluorescent pseudomonads to produce IAA. The results obtained showed that the fluorescent pseudomonads isolates Pf31, Pf32, Pf33, Pf35, Pf36, Pf37, Pf38, Pf39, and Pf40 had the ability to produce IAA with the highest concentration produced by isolate Pf36 which was 9.86 ppm and the lowest concentration was produced by isolate Pf38. ie 3.65 ppm.